2016
DOI: 10.1097/acm.0000000000001219
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Publication Productivity, Academic Rank, and Career Duration Among U.S. Academic Gastroenterology Faculty

Abstract: A gender gap exists in the number and proportion of women in academic GI; however, after correcting for career duration, productivity measures that consider quantity and impact are similar for male and female faculty. Women holding senior faculty positions are equally productive as their male counterparts. Early and continued career mentorship will likely lead to continued increases in the rise of women in academic rank.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 17 publications
(27 reference statements)
1
59
1
1
Order By: Relevance
“…Due to the small sample size of some of the later career subgroups, this analysis may be underpowered, and therefore statistical differences may actually exist between men and women in these groups. However, as mentioned previously, prior studies have demonstrated that women tend to “catch up” with their male counterparts in the later career period …”
Section: Discussionmentioning
confidence: 81%
“…Due to the small sample size of some of the later career subgroups, this analysis may be underpowered, and therefore statistical differences may actually exist between men and women in these groups. However, as mentioned previously, prior studies have demonstrated that women tend to “catch up” with their male counterparts in the later career period …”
Section: Discussionmentioning
confidence: 81%
“…35 Female physicians’ increased time commitments to home and child-bearing and rearing responsibilities, coupled with male physicians’ longer career durations, offer alternative potential explanations for this discrepancy in academic productivity. 20,21,23,36,37 Finally, another explanation may be that females are more likely to pursue career advancement through clinical excellence and teaching responsibilities, which are more difficult to objectively quantify and are not accounted for in the h-index. For example, lower rates of academic productivity among female surgical oncologists may originate from differential career choices of faculty track (i.e., research vs. clinical track).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in gastroenterology, otolaryngology, ophthalmology, and radiation oncology have confirmed a systematic gender association with academic position. 79, 14 Urology is no exception to these trends. Our results confirm previous findings where women tend to plateau at the rank of associate professor.…”
Section: Discussionmentioning
confidence: 99%